Individual MHCI-Restricted T-Cell Receptors are Characterized by a Unique Peptide Recognition Signature - Wooldridge, Linda (Frontiers in Immunology, 2013)
Effective immunity requires that a limited TCR repertoire is able to recognize a vast number of foreign peptide-MHCI. This challenge is overcome by the ability of individual TCRs to recognize large numbers of peptides. Recently, it was demonstrated that MHCI-restricted TCRs can recognize up to 10^6 peptides of a defined length. Astonishingly, this remarkable level of promiscuity does not extend to peptides of different lengths, a fundamental observation that has broad implications for CD8+ T-cell immunity. In particular, the findings suggest that effective immunity can only be achieved by mobilization of "length-matched" CD8+ T-cell clonotypes. Overall, recent findings suggest that every TCR is specific for a unique set of peptides, which can be described as a unique "peptide recognition signature" and consists of three components: 1) peptide length preference, 2) number of peptides recognized; and, 3) sequence identity (e.g. self versus pathogen derived). In future, the ability to deconvolute peptide recognition signatures across the normal and pathogenic repertoire will be essential for understanding the system requirements for effective CD8+ T-cell immunity and elucidating mechanisms which underlie CD8+ T-cell mediated disease.